Single Parent in Developing Children Character (Case Study on Students at Madrasah Tsanawiyah Ma'arif Kawedusan Pongok Blitar) - Rizka Khuswanal Mala (Didaktika Religia, 2017)
The focus of in this study is examining (1) the role of single mother and single father in developing the character of the children; (2) character of sons and daughters who are under the care of single mothers; (3) character of sons and daughters who are under the care of single fathers. This research uses qualitative method in the form of case study. The location of this research is, first, MTs Ma'arif Kawedusan Ponggok Blitar. Second, the home of the children and the single parent in Ponggok. Data source used is primary data source and secondary data. Data collection techniques used is observation, interview and documentation. The data validity technique uses source triangulation. Qualitative data analysis uses data analysis techniques proposed by Miles and Huberman. The results showed that there are three aspects of single parent roles: motivator, facilitator, and mediator. The facilitator and mediator aspects are the most frequently performed by single parent, while the aspect of the motivator is the least done by a single parent. This is because a single parent is more focused on the economic condition of the family. Single mothers are better able to portray the three aspects of roles as motivators, facilitators, and mediators than parent fathers.